Promotor engineering in Saccharomyces cerevisiae for transcriptional control under different physiological conditions - Conradie, E. C. (Elizabeth Cornelia) (Stellenbosch : University of Stellenbosch, 2011)
Dissertation (PhD)--University of Stellenbosch, 2005.